Applications of latent-variable models in educational psychology: The need for methodological-substantive synergies - Marsh, H; Hau, K (2007)
As emphasized in the call for papers by Jonna Kulikowich and Gregory Hancock, the primary goal of this special issue of Contemporary Educational Psychology is to assemble a collection of illustrative empirical studies in educational psychology that utilize one or more state-of-the-art latent variable modeling procedures. Distinguishing these articles from those in leading measurement and statistical journals, Kulikowich and Hancock encouraged the submission of manuscripts from authors (or teams) with strong backgrounds in both latent variable methodology and substantive issues in educational psychology. In this respect, they sought to provide an outlet for articles representing a synergy between sophisticated methodology and meaningful substantive issues. Here we briefly review why we think that this is such an important undertaking; consider some of the problems that such undertakings must address; emphasize a construct validity approach to the interpretations based on such studies; and highlight some of the key issues in the particular articles in this special issue. © 2006 Elsevier Inc. All rights reserved.